Investigations of interfacial engineering on MgO-based resistive switching memory devices - Chow, Samuel Chen Wai (Nanyang Technological University, 2023)
The shift towards data-centric and energy-efficient consumer electronics has presented challenges to the current computing paradigm. Although advancements have been made through multiprocessing and multithreading, limitations in logic-memory performances and complimentary metal-oxide-semiconductor (CMOS) scaling still exist. Therefore, there is a demand for emerging non-volatile memories (NVM) with high performance, low energy consumption, and excellent reliability. Notably, resistive random-access memory (ReRAM) has demonstrated the potential to overcome the immediate concerns of modern computational processes owing to its high scalability, fast switching speed, and low switching energy. However, the inherent stochasticity and thermal stability due to the switching mechanisms involved hinder the commercialization of the memory device. Magnesium oxide (MgO) has been of great interest in magnetic tunnel junctions (MTJs) and has shown great promise in ReRAM due to its dielectric properties. This thesis focuses on developing MgO-based resistive switching memory for improved variability, low-power, and thermally stable applications by exploring the electrical, compositional, and structural properties and conduction mechanisms of the device. The study of MgO/Al2O3-based bilayer ReRAM devices indicates that the stack configuration contributes to enhanced filamentary confinement at the bilayer interface. This reduced oxygen-deficient region promotes filament rupture and generation at the interface, decreasing variation while increasing the high and low resistance state (HRS and LRS) values. Furthermore, the shift in conduction mechanisms from space-charge-limited conduction (SCLC) in single-layer MgO devices to Schottky emission (SE) in bilayer devices was revealed, describing the change in activation energies due to oxygen vacancy migration. The top electrode (TE) was further explored to observe the intermediate oxide layer formation response as a consequence of oxygen affinity modulation between MgO and TE. Moreover, indexing of these various TE was performed based on the C-V characteristics. The findings show an increase in the ON/OFF ratio with improved switching uniformity when controlling the interfacial reactions between the TE and MgO. The heat treatment effects were correspondingly investigated for the development of thermally stable resistive switching behaviour in MgO-based resistive switching memory. In addition, the area and compliance current (CC) dependence of the devices were further examined for potential CMOS integration. These findings demonstrate the switching dynamics of interfacial engineering in MgO-based resistive switching memory devices, which will provide a comprehensive understanding for future utilization in cross-point structures.